Divided loyalties : a reconciling ethic for churches in Northern Ireland - Carroll, Lesley Elizabeth (Irish School of Ecumenics, 2006)
Can a denomination publicly engage with those who are different and maintain its own theological integrity? Can a biblically, theologically and ecumenically informed ethic be developed to sustain a denomination in such engagement? These questions are at the heart of this thesis and arise out of a theological concern that churches find ways to publicly bear witness to the gospel, specifically in Northern Ireland, seeking fuller conversion to God and the transformation of society. In situations, like that in Northern Ireland, where there is cultural and ethnic competition, the ethic will necessarily be a reconciling ethic.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin